Three-Layered Closure of Persistent Oroantral Fistula Using Chin Graft, Buccal Fat Pad, and Buccal Advancement Flap: A Case Report with Review of Literature - Shiv Prasad Sharma (Hindawi Limited, 2019)
Various techniques have been used for the repair of oroantral fistula (OAF) but majority of them have focused on the soft tissue closure alone, and most of the time, the osseous floor of the sinus was ignored. Existing literature supports that bone grafts supported by Buccal Fat Pad (BFP) heal well without undergoing significant resorption and necrosis. Through this case report, we wish to elaborate on the clinical success of using BFP and autogenous chin graft for simultaneous reconstruction of a large long-standing oroantral fistula with underlying osseous defect. The combination technique can prove beneficial for osseous regeneration of sinus floor and improve chances for future implant prosthetic rehabilitation.